POLA ALIRAN AIR BAWAH TANAH DI PERUMNAS GRIYA BINA WIDYA UNRI MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI ELEKTRODA SCHLUMBERGER - Edisar, Muhammad; Damayana, Listia (Komunikasi Fisika Indonesia, 2016)
The research about groundwater flow pattern in Perumnas Griya Bina Widya UNRI Tampan subdistrict of Pekanbaru have been done. Groundwater flow pattern mode from one dimension geoelectric data of Schlumberger electrode configuration. Based on formation of lithology resulted from geoelectric data, resulted four formation of lithology from block A to block G of the Perumnas. From the mapping resulted groundwater flow pattern on the first formation layer groundwater flow from northeast to south the to the southwest with 10 â 39.1 meters of thickness of layers. On the second formation groundwater flow from the northeast to north the to the south with 8 â 52.8 meters of thickness of layers. The groundwater flow thrith layers from the northeast to the southeast thickness in this layers 2.5 â 75.8 meters. Forwhile groundwater flow on the fourth layers from the north to the southeast by the thickness from 3.5 â 79.1 meters.